2006
DOI: 10.1128/jb.188.7.2593-2603.2006
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Effect of theStaphylococcus aureusVirulence Factor Regulator, SarA, on Log-Phase mRNA Half-Lives

Abstract: Bacterial pathogens regulate virulence factor expression at both the level of transcription initiation and mRNA processing/turnover. Within Staphylococcus aureus, virulence factor transcript synthesis is regulated by a number of two-component regulatory systems, the DNA binding protein SarA, and the SarA family of homologues. However, little is known about the factors that modulate mRNA stability or influence transcript degradation within the organism. As our entree to characterizing these processes, S. aureus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
117
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(129 citation statements)
references
References 62 publications
10
117
2
Order By: Relevance
“…1) indicate that log-phase transcripts are degraded rapidly within mock-treated cells; 89.7% of all transcripts had half-lives of Յ5 min, 206 transcripts (9.2%) had intermediate half-lives (Ͼ5 min but Յ30 min), and 25 (1.1%) RNA species were stable (half-lives of Ͼ30 min). These results are in agreement with previous studies using custom-made S. aureus GeneChips (Saur2a), which found that the half-lives of 89.6% of all UAMS-1 log-phase transcripts were Ͻ5 min, those of 9.5% of transcripts were intermediate, and those of 0.7% of transcripts were stable (Ͼ60 min) (46). Induction of the SOS response did not appreciably affect global RNA turnover properties, whereas induction of the heat shock, cold shock, and stringent responses appeared to dramatically stabilize RNA species (Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…1) indicate that log-phase transcripts are degraded rapidly within mock-treated cells; 89.7% of all transcripts had half-lives of Յ5 min, 206 transcripts (9.2%) had intermediate half-lives (Ͼ5 min but Յ30 min), and 25 (1.1%) RNA species were stable (half-lives of Ͼ30 min). These results are in agreement with previous studies using custom-made S. aureus GeneChips (Saur2a), which found that the half-lives of 89.6% of all UAMS-1 log-phase transcripts were Ͻ5 min, those of 9.5% of transcripts were intermediate, and those of 0.7% of transcripts were stable (Ͼ60 min) (46). Induction of the SOS response did not appreciably affect global RNA turnover properties, whereas induction of the heat shock, cold shock, and stringent responses appeared to dramatically stabilize RNA species (Fig.…”
Section: Resultssupporting
confidence: 93%
“…To do so, either log-phase UAMS-1 cells were mock treated or the corresponding stress response was induced (conditions described above). Rifampin was then added to inhibit de novo transcript synthesis, as previously described (46). Aliquots were removed at 0, 2.5, 5.0, 15, and 30 min post-transcriptional arrest, and cell viability and rifampin resistance were measured (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA binding and profiling studies suggest that the SarA protein may regulate target genes by directly binding to target gene promoters or indirectly via downstream effects on regulons (e.g. binding to the agr promoter) or by stabilizing mRNA during log phase (Cheung et al, 2004;Roberts et al, 2006).…”
Section: Structure Of the Sara Protein Familymentioning
confidence: 99%